The influence of institutionalization on the perception of autonomy and quality of life in old people - Carmen María Sarabia Cobo (SciELO, 2014)
Objective To evaluate the influence exercised by institutionalization on the autonomy and perception of quality of life among the institutionalized elderly. Method The study is quasi-experimental (interrupted time series) and longitudinal. The sample is composed for 104 elderly people who went into a three nursing home in Santander, Spain. To assess the quality of life and dependence two scales were used: the Barthel Index and Lawton Index. Results There was an important relationship between autonomy and independence and their deterioration due to their institutionalisation, such as the physical and social aspects. Conclusion It´s important to point out that the dependence of the elderly is a complex phenomenon, which admits many types of intervention, including the customary ones referring to more classic welfare actions which tend to supplant the absence of autonomy in everyday life by facilitating services and attention to make up for this need, without having to resort to institutionalization.